The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s003300100963
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound examination of carotid and vertebral arteries

Abstract: Ultrasound is the most widespread diagnostic procedure in obstructive disease of the arteries supplying the brain. The combined non-invasive information on morphology and function makes duplex ultrasound the procedure of choice in screening and follow-up of carotid artery disease. This review deals with all relevant aspects of color duplex ultrasound of the carotids and the vertebral arteries. After a short introduction into the clinical background, the paper focuses on aspects of examination technique. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 51 publications
0
29
0
2
Order By: Relevance
“…Stenoses of common, internal, and external carotid artery were measured as a reduction of luminal area and graded with consideration of all information from B-mode, pulsed-wave, and color-flow Doppler according to established criteria. 28,29 Anterior, middle, and posterior cerebral artery, vertebral and basilar arteries, and distal internal carotid artery were evaluated on the basis of peak systolic flow velocities by transcranial Doppler. Identification of the arteries and definition of normal velocities were based on published criteria.…”
Section: Preoperative Assessment Of Potential Sources Of Embolismmentioning
confidence: 99%
“…Stenoses of common, internal, and external carotid artery were measured as a reduction of luminal area and graded with consideration of all information from B-mode, pulsed-wave, and color-flow Doppler according to established criteria. 28,29 Anterior, middle, and posterior cerebral artery, vertebral and basilar arteries, and distal internal carotid artery were evaluated on the basis of peak systolic flow velocities by transcranial Doppler. Identification of the arteries and definition of normal velocities were based on published criteria.…”
Section: Preoperative Assessment Of Potential Sources Of Embolismmentioning
confidence: 99%
“…Stenoses of the common, internal, and external carotid arteries were measured as reduced diameter and were graded with consideration of all information from B-mode, pulsed-wave, and color flow Doppler. 19 Carotid stenoses were considered significant if there was Ͼ70% diameter reduction.…”
Section: Preoperative Assessment Of Potential Sources Of Embolismmentioning
confidence: 99%
“…32 Other authors reported an overall sensitivity of 91% to 95% and specificity of 86% to 97%. 1 Color and duplex Doppler sonography and DSA have shown agreement in at least 90% of the cases in the grading of stenosis. 45,46 The complication rate for DSA is 1% to 2% for both stroke and death.…”
Section: Comparison Of the Diagnostic Value Of Color Duplex Sonographmentioning
confidence: 95%
“…Four of 5 of the ischemic events are caused by atherosclerotic diseases, with most changes affecting the carotid bifurcation. 1 Two randomized studies, the North American Symptomatic Carotid Endarterectomy Trial (NASCET) and the European Carotid Surgery Trial (ECST), were performed in symptomatic patients to examine the efficacy of carotid endarterectomy (CEA) in patients with highgrade (≥70%) internal carotid artery (ICA) stenosis based on the angiographic estimation of the degree of stenosis. It was proved that these patients did benefit from carotid surgery compared with the group receiving conservative treatment.…”
mentioning
confidence: 99%